There is no territorial fatality! (or how innovation interactions between KIBS and SMEs may modify the development patterns of peripheral regions) - Emmanuel Muller (Fraunhofer-Institut für System- und Innovationsforschung ISI, 1999)
Observing regions, for instance in Europe, one may easily notice inequalities in the resources they devote to innovation activities and in the results they reach in terms of economic success. In this respect, it may be assumed at first glance that a hierarchy of regional environment could be established. Nevertheless, it is advocated in the paper that this does not obligatorily imply a "territorial fatality". More precisely, the analysis constitutes an attempt to highlight the role of actors who have been insufficiently taken into account by comparison to the ones traditionally examined: large companies, universities and other higher education institutions, technology transfer organisations, regional administrations and other public bodies. The actors on which the paper focuses are: (i) small and medium-sized manufacturing firms (SMEs); and (ii) knowledge-intensive business services (KIBS). In particular the case of SMEs is of interest since SMEs represent the largest proportion of manufacturing firms located in peripheral regions (and in certain peripheral regions, the whole population of manufacturing firms). For similar reasons, it seems relevant to examine also KIBS. The expansion of KIBS reflects the growing importance of their economic activity. Moreover, they are locally available even in regions with no or only little traditional innovation infrastructure. Additionally, the hypothesis is made that potentially the virtuous circle linking the innovation activities of SMEs and KIBS may compensate the impact of less favourable regional environments. The paper contains two main sections. The first section establishes the theoretical framework of the analysis. At first, the nature of the innovation phenomenon is examined, stressing its interactive character. Then, since some regional environments seem to be more favourable to innovation than others, the question of territorial fatality is addressed. In this respect, the concept of a regional hierarchy featuring the inequality between environments in terms of innovation support is introduced. Finally, two models sketching interactions implying KIBS are discussed: the first arguing that the development of KIBS reinforces the domination of core regions, the second showing a possibility for peripheral regions to escape from territorial fatality thanks to the virtuous circle of innovation linking potentially KIBS and SMEs. The second section examines empirical results. With the help of three distinct statistical treatments, the regional innovation hierarchy is contested. In fact, the empirical evidence establishes that the influence of the type of regional environment is negligible compared to other determinants. Considering that SMEs and KIBS mutually benefit from the virtuous circle associating them, the consequences regarding regional evolution patterns are discussed in the concluding section.
urn:nbn:de:0011-n-17776
Keywords: 330; Innovation; Regionale Entwicklung; Kern-Peripherie-Beziehung; Strukturschwacher Raum; Unternehmensdienstleistung; Wissenstransfer; Klein- und Mittelunternehmen; Lieferanten-Kunden-Beziehung; Theorie; Elsaß; Baden